Take the 2-minute tour ×
Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. It's 100% free, no registration required.

I would like to have an example (or a proof that there does not exist) of a function on the complex numbers, which for lack of a better term I'll call generalized addition, such that $$x\oplus y=y\oplus x$$ $$(x\oplus y)\oplus z=x\oplus(y\oplus z)$$ $$x\oplus (\pm i\cdot x)=0$$ $$(ax)\oplus(bx)=(|a|+|b|)x\oplus 0$$

Where $a$ and $b$ are real. Actually, it would be even nicer is the last identity could be substituted with $$(ax)\oplus(bx)=f(|a|+|b|)x\oplus 0$$ where $f(|a|+|b|)\ge (|a|+|b|)^\alpha$ and $\alpha\ge 1$. An example of a function that satisfies the first three identities (but not the forth one) is $x\oplus y=\sqrt(x^2+y^2)$. Is there a way to incorporate the last condition?

EDIT: Continuity would be nice, bar a(n almost necessary) branch cut.

EDIT: Changed the fourth condition since it seems to lead to a trivial contradiction.

share|improve this question
    
Any further constraints on $\oplus$? Should it, say, be continuous? –  Johannes Kloos May 4 '12 at 21:14
    
Thanks, I added it in the statement of the problem. –  Ivan May 4 '12 at 21:18
2  
"Generalized addition" is not a very good name for it unless it's a generalization of addition. "A is a generalization of B" usually means every B is an A but not every A is a B. That would mean every instance of addition is an instance of "generalized addition". But that's inconsistent with the properties you specify. –  Michael Hardy May 4 '12 at 21:42
2  
From the fourth property alone: $x = x \oplus 0 = (-(-x)) \oplus 0 = -x$ for any complex number $x$. –  D. Thomine May 4 '12 at 22:04
2  
A trivial example: $x \oplus y = 0$ for all $x,y$. –  Robert Israel May 5 '12 at 0:15
show 7 more comments

1 Answer

up vote 4 down vote accepted

Suppose $x \oplus y$ is of the form $h\big(g(x) + g(y)\big)$ with $g\big(h(x)\big) = x$, which immediately guarantees commutativity and associativity: $$x \oplus y = h\big(g(x) + g(y)\big) = h\big(g(y) + g(x)\big) = y \oplus x,$$ $$(x\oplus y)\oplus z = h\big(g(h\big(g(x) + g(y)\big))+g(z)\big) = h\big(g(x) + g(y) + g(z)\big) = h\big(g(x) + g(h\big(g(y) + g(z)\big))\big) = x\oplus(y\oplus z).$$ Now let $g(x)$ be the complex number with the same modulus as $x$ and twice its argument. That is, $g(0) = 0$, and $g(x) = \lvert x\rvert e^{2i\arg x}$ when $x \ne 0$. Then we can set $h(0) = 0$ and $h(x) = \lvert x\rvert e^{i(\arg x)/2}$ otherwise. Assuming $\arg$ has range $(-\pi,\pi]$, this has a discontinuity along the negative real line, and we have $g\big(h(x)\big) = x$, but $h\big(g(x)\big) = x \operatorname{sgn} \operatorname{Re} x$. Now observe that $$g(\pm ix) = e^{\pm i\pi}\lvert x\rvert e^{2i\arg x} = -g(x),$$ and for real $a$, $\arg ax$ is either $\arg x$ or $\arg x \pm \pi$ depending on the sign of $a$, but in either case $$g(ax) = \lvert a\rvert\lvert x\rvert e^{2i\arg x}e^{\pm2i\pi} = \lvert a\rvert g(x).$$

Now we can verify the third and (original) fourth conditions: $$x\oplus(\pm ix) = h\big(g(x) + g(\pm ix)\big) = h\big(g(x) - g(x)\big) = h(0) = 0.$$ $$(ax)\oplus(bx) = h\big(g(ax)+g(bx)\big) = h\big(\lvert a\rvert g(x) + \lvert b\rvert g(x)\big) = h\big((\lvert a\rvert + \lvert b\rvert)g(x)\big) = h\big(g((\lvert a\rvert+\lvert b\rvert)x)\big) = h\big(g((\lvert a\rvert+\lvert b\rvert)x) + g(0)\big) = (\lvert a\rvert+\lvert b\rvert)x \oplus 0.$$

(I don't understand why the original fourth condition is troublesome or implies that $x \oplus 0 = 0$. Perhaps there is an error in this answer.)

share|improve this answer
    
@anon, the question states that the fourth identity applies to real-valued $a$ and $b$. Commutativity and associativity follow immediately from the form of $x \oplus y = g(x) + g(y)$; I'll edit that into the answer. –  Rahul May 5 '12 at 1:35
    
Sorry, you're right, I forgot that $a,b$ must be real! I see commutativity immediately, but how do you get associativity quickly? Wouldn't that involve e.g. $$g(g(x)+g(y))+g(z)=g(x)+g(g(x)+g(y))~?$$ That looks like a mess.. –  anon May 5 '12 at 1:37
    
@anon: Oops. $\ $ –  Rahul May 5 '12 at 1:42
    
@anon, I think I fixed it. Can you check? –  Rahul May 6 '12 at 1:39
    
Your solution is correct, I made a mistake in my last edit, there is no problem with the last statement in its current form. –  Ivan May 6 '12 at 4:30
show 2 more comments

Your Answer

 
discard

By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.